ROE and Value Creation under IAS/IFRS: Evidence of Discordance from French Firms - Mohamed El Hedi Arouri; Aldo Lévy; Duc Khuong Nguyen (European Financial and Accounting Journal, 2010)
This paper re-examines the effects that adoption of the International Financial Reporting Standards (IFRS) has had on financial reporting of French listed firms. By analysing the 2004 financial statements of CAC 40 companies, we show that the transition to the IAS/IFRS has a significant impact on the return on equity (ROE) of considered firms by increasing it by 25 basis points on average, compared to the French GAAP. This finding thus suggests an amplified degree of discordance between the ROE, as a crucial measure of firm performance, and the value creation process following the IFRS adoption. From a theoretical viewpoint, Merton (1987)'s capital asset pricing model (CAPM) with incomplete information, which claims its convergence to its traditional version through the reduction of information costs, cannot in fact be valid, owing to divergences in the assessment of a firm's performance.
Keywords: L25; M41; 650; IAS/IFRS; Return on equity; Financial leverage